Romanticism in Salafi Da'wah: A Cultural and Historical Perspective from West Sumatra, Indonesia - Sarwan, Sarwan; Meirison, Meirison; Karni, Awis; Yusoff, Kamaruzaman; Bin Mohd Nasir, Badlihisham (SCAD Independent, 2025)
This study examines the Salafi doctrine, which emphasizes the importance of returning to the Qur’an and hadith based on the understanding of Salafus Shalih (the pious predecessors). Using a descriptive qualitative approach, the article focuses on Salafi religious practices in West Sumatra, analyzing how Salafis interpret and implement the sunnah in a contemporary context. Data were collected through interviews, observations, and documentation, and analyzed by categorizing the information into subtopics to extract deeper meanings. The findings indicate that the kajian sunnah (study of the sunnah) among Salafis in West Sumatra is characterized by exclusivity, doctrinal rigidity, and a textual approach. Moreover, the study reveals that the doctrine of adhering to the understanding and practices of Salafus Shalih serves as the cornerstone of Salafi da’wah strategies. This doctrine positions the Salafus Shalih generation as the ideal model for understanding and connecting with the essence of the Qur’an and hadith. The study concludes that the romanticization of Salafus Shalih functions as a central da’wah strategy for Salafi groups, facilitating the mobilization of their religious understanding and practices within contemporary society.